(untitled) (Journal of Engineering, 2009)
This work includes a numerical investigation of steady two dimensional laminar natural convection heat transfer in glazed rectangular enclosure at different tilt angles ranged from (0o to 90o) for Rayleigh number (103-106), aspect ratios(4,5, and 8),and Prandtl number (0.7). The study considers the effect of different boundary conditions on the heat transfer within the enclosure. The continuity equation, Navier-Stokes equations and the energy equation are solved by developing a numerical model based on finite volume method using SIMPLE algorithm with hybrid scheme to compute the velocity vectors, temperature, pressure, and Nusselt No. (local and average). Results show an increase in heat transfer rate with increasing of Rayleigh number, and for low Rayleigh numbers, the conduction is the dominant heat transfer mode. At Ra= 103, the mean Nusselt number remains constant around unity for all cases. The tilt angle has the major effect on the heat transfer for Rayleigh number larger than 104. A comparison of the present results with previously published data is conducted, and good agreement is seen to indicate the effectiveness and flexibility of the developed numerical procedure.